Longitudinal Ultrasound Velocity and Attenuation in Isotopically Enriched Cadmium - Bulatov, A.S.; Kovtun, G.P.; Klochko, V.S.; Korniets, A.V.; Solopikhin, D.A.; Shcherban, A.P. (Металлофизика и новейшие технологии, 2018)
The results of the acoustic-properties’ study of high-purity (>99.999%) cadmium enriched to 66.4% with the isotope ¹⁰⁶Cd and to 82.2% with the isotope ¹¹⁶Cd are presented for the temperature range of 77–300 K. Isotopic effects are observed in the temperature dependence of the 50 MHz ultrasound propagation velocity and attenuation. A comparison of the sound velocity data for the ¹⁰⁶Cd and ¹¹⁶Cd samples has revealed a first-order isotopic effect with a characteristic linear dependence on the isotopes’ masses difference, and it determines the phonon-spectrum change caused by the isotope composition. Measuring the attenuation of the longitudinal ultrasound made it possible to detect a second-order isotopic effect with a quadratic dependence on the isotopes’ masses difference. The quadratic effect is due to a disordered isotope distribution, and it causes an additional relaxation mechanism for phonon scattering. Представлены результаты исследования акустических свойств высокочистого (>99,999%) кадмия, обогащённого до 66,4% по изотопу ¹⁰⁶Cd и до 82,2% по изотопу ¹¹⁶Сd, в температурной области 77–300 К. Изотопические эффекты наблюдались на температурной зависимости скорости распространения и затухания ультразвука частотой 50 МГц. Сравнение данных для скорости звука образцов ¹⁰⁶Cd и ¹¹⁶Сd выявляет изотопический эффект первого порядка с характерной линейной зависимостью от разности масс изотопов и определяет изменение фононного спектра с изотопным составом. Измерение затухания продольного ультразвука позволило обнаружить изотопический эффект второго порядка с квадратичной зависимостью от разности масс изотопов. Квадратичный эффект связан с неупорядоченным распределением изотопов и обусловливает дополнительный релаксационный механизм рассеяния фононов. Представлено результати дослідження акустичних властивостей високочистого (>99,999%) кадмію, збагаченого до 66,4% ізотопом ¹⁰⁶Cd і до 82,2% ізотопом ¹¹⁶Сd, у температурній області 77–300 К. Ізотопічні ефекти спостерігалися на температурній залежності швидкости поширення та згасання ультразвуку частотою у 50 МГц. Порівняння даних для швидкости звуку зразків ¹⁰⁶Cd і ¹¹⁶Сd виявляє ізотопічний ефект першого порядку з характерною лінійною залежністю від ріжниці мас ізотопів і визначає зміну фононного спектру з ізотопним складом. Міряння згасання поздовжнього ультразвуку уможливило виявити ізотопічний ефект другого порядку з квадратичною залежністю від ріжниці мас ізотопів. Квадратичний ефект пов’язаний з неупорядкованим розподілом ізотопів і зумовлює додатковий релаксаційний механізм розсіяння фононів.